Hubungan Antara Tingkat Pengetahuan Ibu dengan Sikap dan Perilaku Ibu Terhadap Pemberian Imunisasi Dasar pada Bayi di Desa Penatih Dangin Puri - Ni Putu Lisa Eka Pratiwi; Luh Seri Ani (Universitas Udayana, 2017)
Twenty seven million children under five years and 40 million pregnant women worldwide have not received routine immunizationservices. The infant mortality rate (IMR) in Indonesia is about 35 per 1000 live births and the under five mortality rate is 46 per1000 children every year. Approximately 1.7 million children death in Indonesia or 5% of death by the age of five in Indonesiawas caused by diseases preventable by immunization. This study is a quantitative research with cross sectional approach. 79mothers with chidren aged 1-4 years old was chosen using purposive sampling from Penatih Dangin Puri village. The researchwas conducted during October to November 2014. Most of the samples show good knowledge (50,6%), good attitude (65,8%)and good behavior (65,8%) regarding immunization. There is a significant relationship (Spearman’s rank correlation, ? = 0,00)between knowledge and attitude regarding immunization. There is a significant relationship between knowledge (Spearman’srank correlation, ? = 0,00) and attitude (Spearman’s rank correlation, ? = 0,00) with behavior regarding immunization.